PERBANDINGAN PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN MODEL PEMBELAJARAN LANGSUNG TERHADAP KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 24 JAMBI - Abdoel Gafar; Firman Tara (Universitas Batanghari Jambi, 2018)
This research aims to: (1) Describe the ability to write news text students are taught using STAD type cooperative learning model and students are taught using direct learning model; (2) Describe the ability to write high-priority student-language text texts that are taught using STAD-type cooperative models and are taught using direct learning models; (3) Describe the ability to write low-priority student-language text texts that are taught using STAD-type cooperative models and are taught using direct learning models, and (4) Describe the interaction of cooperative learning model type STAD and initial ability to the ability to write news text of students of class VIII SMP Negeri 24 Jambi. The type of this research is quantitative with 2x2 factorial experimental designs. The population of the research is the students of class VIII SMP Negeri 24 consisting of 6 classes. The sample of this research is class VIIIA for experiment class with 40 students and class VIIIB for control class with 38 students. Sample determination is determined by purposive sampling technique. The data of students' news text writing capability was obtained using performance test and analyzed using two ways Anova test. Based on the results of this study, it can be concluded that STAD type cooperative learning model affects the ability to write student news text. The effect can be explained as follows. First, the ability to write news texts of students taught using STAD type cooperative learning model is better than students taught using direct learning model. Second, the ability to write high-priority students' text news taught using STAD type cooperative models is better than students taught using direct learning models. Third, the ability to write low-priority students' text taught using STAD type cooperative models is better than students being taught using direct learning models. Fourth, there is no interaction between STAD type cooperative learning model and initial ability to write news text skills of students of class VIII SMP Negeri 24 Jambi.Keywords: Writing News Texts, Cooperative Learning, Direct Learning